Keterampilan Bertanya Guru dan Respon Siswa Ditinjau dari Pola Asuh Orang Tua Siswa pada Mata Pelajaran Sains - Nurhaty Purnama Sari; Wilda Fasim Hasibuan (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
This research aims to describe teacher's inquiring skills and student responses are reviewed by parenting style of students on science subjects in primary school in Batam. The research was analyzed using qualitative and descrivtive quantitative method. The results showed that the teacher's inquiring skills were quite good. Teachers neededto improved advance inquiring skill in changing the demands of the cognitive level in answering questions from the lowest to the highest level. Teacher needed to improve in probing technique. Several teachers were dominant in providing facts, narrow, convergent, and understand level of questions. The student's response to the teacher's questions showed: (a) categories of student answers were dominated by scientific answers, semi-scientific, zero and false; (b )Not many students could not answer (when teachers asked all students; (c) more students gave answers simultaneously; (d) few students were appointed but unable to answer; (e) many of the appointed students were able to answer; (f) students were confuse to give the right answers on practical learning; (g) few students showed to answered questions and asked the teacher. Data of teacher’s inquiring point (g) were resulted by authoritarian parenting style and showed by the quitionare that 94.83% of their authoritarian parentig style, 18,53% of permissive parenting, and 9,81% of authoritative parenting. It meant authoritarian parenting produced a child who was less confident in his ability that caused of the student could not and would not answer and ask the teacher individually.